2020
DOI: 10.3390/nu12061759
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Diet, Menstrual Pain and other Menstrual Characteristics among Spanish Students

Abstract: This study sought to describe and compare adherence to the Mediterranean diet and consumption of local foods from the Huelva region among Spanish university women in relation to menstrual pain and other menstrual characteristics. This cross-sectional study included 311 health science students. The study variables were sociodemographic and gynecologic characteristics, adherence to the Mediterranean diet using the KIDMED questionnaire, alcohol consumption (SDU) and consumption of local food. A descriptive bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 52 publications
1
34
0
2
Order By: Relevance
“…In addition, previous studies indicate that even women who perceive that their cycles are not normal usually fail to consult professionals as they believe that they will not assign any importance to these symptoms, or because of feelings of shame, or fear of being stigmatized by their close environments [ 15 ]. However, health professionals can assist these women in a number of ways, including reporting the available scientific evidence on lifestyle factors that positively and negatively influence menstrual characteristics and symptoms [ 11 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies indicate that even women who perceive that their cycles are not normal usually fail to consult professionals as they believe that they will not assign any importance to these symptoms, or because of feelings of shame, or fear of being stigmatized by their close environments [ 15 ]. However, health professionals can assist these women in a number of ways, including reporting the available scientific evidence on lifestyle factors that positively and negatively influence menstrual characteristics and symptoms [ 11 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the prevalence of dysmenorrhea has been estimated at 73.8–74.8% among university students [ 9 , 10 ]; corresponding to about 63.3% affected by primary dysmenorrhea and 10.5% by secondary dysmenorrhea [ 10 ]. In addition, other menstrual disorders, such as hypermenorrhea, menstrual irregularity, and other menstrual symptoms are less explored, both internationally and in Spain [ 11 , 12 ]. The aims of the published studies are very heterogeneous, although most focus on the prevalence, risk, protective factors, and impacts on their lives [ 4 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sugar consumption also influences insulin resistance and hyperandrogenism in the context of the physiopathology of polycystic ovarian syndrome, increasing the risk of additional metabolic problems [ 40 ]. In relation to the risk of alcohol consumption, this was significant, and greater among women with menstrual problems, along the lines of a study by Yesuf et al in Ethiopian university women and a study by Onieva-Zafra et al among nursing Spanish students [ 31 , 41 ]. However, other studies have reported inconclusive results relating this type of consumption and menstrual problems [ 3 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other types of diet such as vegetarian diets may constitute a protective factor for dysmenorrhea, based on the fact that these diets tend to be lower in fat, with lower oestrogen and high omega-3 [ 21 , 47 ]. The characteristics of the Mediterranean diet, due to its anti-inflammatory potential and contribution to normal weight, has also been identified as being beneficial for some problems such as polycystic ovary syndrome and dysmenorrhea [ 31 , 48 ]. Skipping breakfast was also identified as a lifestyle characteristic that was more common in the women of our study who suffered from menstrual problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation